Evaluation of Podoplanin in Oral Leukoplakia and Oral Squamous Cell Carcinoma - Ashok Patil; Kishor Patil; Suyog Tupsakhare; Mahesh Gabhane; Shrikant Sonune; Shilpa Kandalgaonkar (Scientifica)
Background. Recent studies have demonstrated that podoplanin was expressed in some dysplastic lesions adjacent to primary oral cancers suggesting that podoplanin expression may occur in early oral tumorigenesis and lymphangiogenesis and therefore is related to tumor growth. The purpose of this study is to determine the role of podoplanin as a biomarker for cancer risk assessment in oral leukoplakia and correlation of podoplanin expression with grades of oral squamous cell carcinoma (OSCC). Materials and Methods. In the present retrospective study, podoplanin expression was investigated immunohistochemically in 40 patients each of oral leukoplakia and OSCC. The scores were analyzed statistically using one-way ANOVA test followed by Tukey HSD. Results. By applying one-way ANOVA test, there was a highly significant increase of the podoplanin expression from mild to severe dysplasia and from well to poorly differentiated OSCC (P<0.01). Statistically highly significant difference was present between scores of mild to moderate dysplasia, moderate to severe dysplasia, well to poorly differentiated OSCC, and moderately to poorly differentiated OSCC (Tukey HSD test, P<0.01). Conclusion. Podoplanin can be used as a biomarker for early oral tumorigenesis and for malignant transformation risk assessment of premalignant lesions and as a tumor progression biomarker for advanced grades of OSCC.